Impact of insidious gastrointestinal blood loss on endurance performance in an elite rower - Treff, G.; Schmidt, W.; Wachsmuth, N.; Steinacker, J. M. (The Journal of Sports Medicine and Physical Fitness, 2014)
Gastrointestinal (GI) blood loss is a possible reason for anemia in athletes. To quantify the impact on endurance performance, we present data of a world-class rower who developed anemia due to GI blood loss but maintained his training volume. Eight months after recording four normal hematological values over 6 months, an anemic state was detected. Total hemoglobin mass (tHbmass) was reduced from 1267 g to 917 g (-28%) and [Hb] was reduced from 176 g/L to 122 g/L (-31%). Blood volume (BV) remained largely unchanged at 8162 mL and 8261 mL, respectively. VO2max was decreased from 5.8 L/min to 4.8 L/min (-17%), but remained ~0.4 L/min higher than calculated from tHbmass. Power at [lactate] 2 mmol/L (P2) and 4 mmol/L (P4) decreased by 12% and 14%, respectively. Ten months after detection of the anemic state, the athlete had recovered and tHbmass (9%) as well as VO2max (3%), P2 (7%) and P4 (5%) were higher than before anemia. GI blood loss was most likely caused by the intake of non steroidal anti-inflammatory drugs and/or a bleeding Meckel's diverticulum, the latter been diagnosed and surgically removed 3 years later after two rapid bleedings had occurred. Data demonstrate the impact of a tHbmass reduction leading to a substantial but mitigated decrease in submaximal performance and VO2max in an elite athlete. 10 months later, higher levels of tHbmass, VO2max, and endurance performance were observed. However, the underlying mechanisms for the apparent increase in tHbmass remain unclear.